Análisis socio-jurídico de los presupuestos que derivan el pago de pensión alimenticia a los obligados subsidiarios en el cantón Arenillas, en los años 2011-2012. Propuesta de reforma al artículo innumerado 5 de la ley reformatoria al código de la niñez y adolescencia. - Rey Betancourt, Mónica Patricia (2013)
This research, prior to obtaining the title of lawyer is dedicated to researching this topic, socio-legal analysis of budgets derived paying alimony to the subsidiary required in the canton Arenillas, in the years 2011-2012 . Unnumbered proposed amendment to Article 5 of the Code Reform Act of childhood and adolescence. The right can be seen as the set of rules governing the relations of men living in society the right to food falls within civil law and within this the Family Law. Foods in Family Law are all indispensable means for a person to meet all your basic needs according to the social position of the family, this right is born with effect parento relationship - subsidiary, look to family law and order and is nontransferable , non-transferable, inalienable, essential and does not support compensation. They are required to provide food, father and mother, brothers who are 18 years, grandparents and uncles.